Intrinsic ferromagnetic and antiferromagnetic axion insulators in van der Waals materials MnX_{2}B_{2}T_{6} family - Yan Gao; Kai Liu; Zhong-Yi Lu (Physical Review Research, 2022)
The MnBi_{2}Te_{4} family has attracted significant attention due to its rich topological states such as the quantum anomalous Hall (QAH) insulator state, the axion insulator state, and the magnetic Weyl semimetal state. Nevertheless, the intrinsic antiferromagnetic (AFM) interlayer coupling in MnBi_{2}Te_{4} partly hinders the realization of the “high-temperature” QAH effect. Here, by using first-principles electronic structure calculations, we design a new class of materials MnX_{2}B_{2}T_{6} (X=Ge, Sn, or Pb; B=Sb or Bi; T=Se or Te) based on the X_{2}B_{2}T_{5} structures rather than the Bi_{2}Te_{3} family. We find that each septuple-layer MnB_{2}T_{4} is sandwiched by two [XT] layers, which may turn the AFM interlayer coupling into a ferromagnetic (FM) coupling. The calculations specifically demonstrate that MnGe_{2}Sb_{2}Te_{6}, MnGe_{2}Bi_{2}Te_{6}, and MnPb_{2}Bi_{2}Te_{6} are FM axion insulators, while MnGe_{2}Sb_{2}Se_{6}, MnGe_{2}Bi_{2}Se_{6}, MnSn_{2}Sb_{2}Te_{6}, and MnSn_{2}Bi_{2}Te_{6} are A-type AFM axion insulators. These seven materials all have an out-of-plane easy axis of magnetization. The MnX_{2}B_{2}T_{6} family thus offers a promising platform beyond the MnBi_{2}Te_{4} family for the realization of the quantized magnetoelectric effect and “high-temperature” QAH effect in future experiments.